2020
DOI: 10.1080/08870446.2020.1811867
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the ticked box: organ donation decision-making under different registration systems

Abstract: Objective: To explore how people experience organ donation decision-making under the conditions of an opt-in, opt-out or noobjection registration system. Design: A between-subjects experimental 3 Â 2 design (registration system x preselection). Participants (N ¼ 1312) were presented with a description of one of the three registration systems and went through a mock donor registration process. In half of the conditions, the default option of the system was visualized by a ticked box. After, participants answere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A strong empirical basis to support claims about these unfavorable effects of nudging on autonomy is lacking. In fact, to date the few studies that have empirically investigated the effect of defaults on autonomy showed no or only marginally negative effects in hypothetical scenarios (Michaelsen, Johansson, & Hedesström, 2021;Wachner, Adriaanse, & De Ridder, 2020a;Wachner, Adriaanse, & De Ridder, 2021), also in case of organ donation (Steenaart, Crutzen, & De Vries, 2021). However, results from hypothetical studies may be very different compared to when people are actually confronted with a default nudge in real life (Wachner et al, 2021;Wachner, Adriaanse, & De Ridder, 2020b).…”
Section: Does Default Organ Donation Registration Compromise Autonomous Choice?mentioning
confidence: 99%
“…A strong empirical basis to support claims about these unfavorable effects of nudging on autonomy is lacking. In fact, to date the few studies that have empirically investigated the effect of defaults on autonomy showed no or only marginally negative effects in hypothetical scenarios (Michaelsen, Johansson, & Hedesström, 2021;Wachner, Adriaanse, & De Ridder, 2020a;Wachner, Adriaanse, & De Ridder, 2021), also in case of organ donation (Steenaart, Crutzen, & De Vries, 2021). However, results from hypothetical studies may be very different compared to when people are actually confronted with a default nudge in real life (Wachner et al, 2021;Wachner, Adriaanse, & De Ridder, 2020b).…”
Section: Does Default Organ Donation Registration Compromise Autonomous Choice?mentioning
confidence: 99%
“…This could explain the higher prevalence of uncontrolled donation after circulatory arrest protocols—which require expeditious organ preservation measures—in opt-out countries as compared with opt-in countries 28 29. Other indirect effects are psychological and behavioural, such as increasing people’s awareness and conversations within families about organ donation, influencing the meaning they assign to donating or not donating,30 altering their registration behaviour,31 32 fostering professionals to identify and refer potential donors and approach their relatives when the deceased failed to register any preference, and changing the conversation between health professionals and relatives 6 33. In Wales, an increase in family authorisation rates could be explained by such indirect factors, including increased societal concern about organ scarcity, growing confidence of families in healthcare professionals, and specialist nurses’ training and familiarity with the legislation 34.…”
Section: Introductionmentioning
confidence: 99%